Regional Arterial Stiffness in Patients with Inflammatory Bowel Disease - V. V. Genkel; R. G. Portnova; T. V. Antipina; I. I. Shaposhnik (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2019)
Aim.  To study muscular (brachial and radial arteries) and elastic (aorta) regional arterial stiffness in IBD patients in comparison with those without IBD, as well as to establish the relationship between arterial stiffness and the characteristics of the IBD course (the duration of illness, severity of attack, activity of systemic inflammation). Materials and methods. The study included 21 IBD patients and 30 patients in the comparison group. The values of regional aortic and muscular arterial stiffness were measured by applanation tonometry. The carotid–femoral pulse wave velocity (cfPWV) and the carotid-radial pulse wave velocity (crPWV) were determined. The laboratory research plan included the analysis of complete blood count, biochemical parameters, fibrinogen and a high sensitivity  C-reactive protein (hsCRP).Results. crPWV, similar to cfPWV, was not significantly different between the groups. At the same time, the proportion of individuals with an increase in the cfPWV of more than 10 m/s was higher in the group of IBD patients. However, these differences did not reach the level of statistical significance. According to the results of the correlation analysis, the increase in cfPWV was associated with an increase in patient age (r = 0.564; p = 0.01), the duration of IBD history (r = 0.628; p = 0.003), fasting plasma glucose (r = 0.367; p = 0.034) and GFR decrease (r = -0.482; p = 0.031). The crPWV also directly correlated with the IBD duration (r = 0.630; p = 0.003). According to the results of the regression analysis, an increase in the IBD duration by 1 year is associated with an increase in cfPWV by 0.205 m/s, i.e. the increase in the IBD duration by 5 years is associated with an increase in the cfPWV of approximately 1 m/s.Conclusion. In IBD patients, the duration of the disease directly correlated with an increase in cfPWV and crPWV. The increase in the IBD duration by 1 year was associated with an increase in cfPWV by 0.205 m/s. The muscular and elastic regional arterial stiffness was not statistically significantly different between IBD patients and the comparison group.